1, 1′‐Diethyl‐4, 4′‐bipyridine‐1, 1′‐diium bis(1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide): multiple C—H...N hydrogen bonds form a complex sheet structure. Issue 3 (15th March 2014) - Setifi, Zouaoui; Lehchili, Fouzia; Setifi, Fatima; Beghidja, Adel; Ng, Seik Weng; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In the title salt, C14H18N22+·2C9H5N4O−, the 1, 1′‐diethyl‐4, 4′‐bipyridine‐1, 1′‐diium dication lies across a centre of inversion in the space group P21/c. In the 1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide anion, the two independent –C(CN)2 units are rotated, in conrotatory fashion, out of the plane of the central propenide unit, making dihedral angles with the central unit of 16.0 (2) and 23.0 (2)°. The ionic components are linked by C—H...N hydrogen bonds to form a complex sheet structure, within which each cation acts as a sixfold donor of hydrogen bonds and each anion acts as a threefold acceptor of hydrogen bonds.